2015
DOI: 10.1159/000369680
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Attenuates Aldosterone-Induced Tubulointerstitial Inflammation and Fibrosis

Abstract: Background/Aim: Aldosterone (Aldo), a mediator of kidney fibrosis, is implicated in the pathogenesis of chronic kidney diseases (CKD). The aim of this study was to evaluate the regulatory role of rapamycin (Rap) in Aldo-induced tubulointerstitial inflammation and fibrosis. Methods: Uninephrectomized, Sprague-Dawley rats were given 1% NaCl (salt) to drink and were randomized to receive treatment for 28 days as follows: vehicle infusion (control), 0.75 μg/h Aldo subcutaneous infusion, or Aldo infusion plus 1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…In the tubulointersitium, tubular epithelial cells are the initial site of injury, and then interstitial fibroblasts are activated [9]. Tubular epithelial cells undergo EMT under many pathophysiological conditions [36]. This process promotes tubular epithelial cell transformation into profibrotic myofibroblasts that express the myofibroblast marker α-SMA [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In the tubulointersitium, tubular epithelial cells are the initial site of injury, and then interstitial fibroblasts are activated [9]. Tubular epithelial cells undergo EMT under many pathophysiological conditions [36]. This process promotes tubular epithelial cell transformation into profibrotic myofibroblasts that express the myofibroblast marker α-SMA [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to producing various ECM proteins, epithelial cells undergo epithelial-mesenchymal transition (EMT) in the presence of certain inflammatory cytokines, thereby promoting the occurrence and development of fibrosis [9]. During EMT, epithelial cells acquire certain characteristics of the stromal cells around them, as seen by the loss of epithelial polarity and the acquisition of stromal features, including a stromal-like appearance, and vimentin, snail, and osteopontin expression [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Vimentin and albumin expression levels also decreased significantly at the gene and protein levels [7]. In addition, Chen et al [9]. demonstrated that TGF-β1 induces EMT in human lung cancer A549 cells, as demonstrated by changes in mesenchymal morphology, increase in invasion and metastasis ability, up-regulation of the mesenchymal marker genes encoding vimentin and fibronectin, and down-regulation of the epithelial marker E-cadherin [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Without any appropriate intervention, it would gradually lead to the conversion of tubulointerstitial inflammation to TIF and worsen renal insufficiency. 3,29 The anti-inflammation property of ozone therapy has been made aware by some researchers. For instance, Alvarez realized ozone therapy could suppress inflammation state of rats suffering from LPS-induced endotoxic shock.…”
Section: Discussionmentioning
confidence: 99%